Socio-Cultural Impact of Herdsmen and Armed Banditry Attacks in Abraka, Delta State, Nigeria - A. O. Edafitohwo; A. C. Ibezute (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to access the socio cultural impact of herdsmen and armed banditary attacks in Abraka, Delta state, Nigeria using appropriate standard structured questionnaires to harvest data from community. Data obtained show that 1% affirmed that attacks had occurred, among those affected, 76% experienced 1–3 attacks, 9% 4–6 attacks, and 15% more than 6 attacks, with 90% indicating that most incidents occurred during 2018–2019. Socio-economically, only 3% and 6% of respondents rated the effect on business as very high and high respectively, whereas 60% reported a very low impact. Most (80%) estimated financial losses in the range of 10,000–999,000 naira over five years, and only 7% reported the loss of a family member. Property losses were notably high for farm assets (46%) and animals (29%). Although 98% noted that security agents did respond, 72% experienced response times exceeding one hour. Ninety-nine percent of respondents recommended deploying more government security agents. These findings highlight the need for enhanced security and revised land-use policies to mitigate long-term socio-economic disruptions.